La carte postale coloniale dans l’album : Nona des sables, un château de cartes mémorielles - Anne Schneider (Strenae)
The picture book Nona des sables by Françoise Kérisel tells the story of young Manuela's investigation into her grandmother Nona’s past, as she asks about memories from Nona’s native Algeria. Using colonial postcards superimposed over text in the picture book, Manuela gradually discovers her family, her Algerian roots, and her mixed identity, through interweaving iconographic and linguistic approaches.